Improving project management monitoring and control: A simulation approach - Omar, Mohamad K.; F.C., Lim (2010)
There is a broad category of Operations Management problems having to do with the management of project type operations. Such operations are typically illustrated by the example of some large-scale, one-time activity such as the design and production of a new prototype machine, the construction of a new facility, or the design and manufacturing of a new system to serve a specific or general propose. The basic approach to all project scheduling is to form an actual or implied network that graphically portrays the tasks and milestone in the project. There are several techniques evolves in the late 1950s for organizing and representing this basic information. Best known today are PERT (Program Evaluation and Review Techniques) and CPM (Critical Path Method).Other network techniques such as PERT/Cost, GERT and Decision CPM are largely extension and modifications of these original two.It is well known and reported in the literature that CPM is best used for situations with a deterministic nature; on the other hand, PERT is best used for stochastic situations. However, although PERT is able to deal with uncertainty in activities times by using three point estimates (optimistic time, most likely time and pessimistic time), the estimate of activity times are clearly subjective and rely solely on judgment. This research paper and through a real life construction project propose a Monte Carlo simulation approach to deal with the short coming problems inherited in the PERT. The results obtained from our comprehensive simulation approach shows that project managers are able to estimate the probability of project completion time and thus allocate contingency plan for the project. In addition, project managers are able to consider the possibility of sub-critical path(s) that might eventually become the critical path as the project progresses through time. The obvious contribution of this research work is the opportunity that provides for project managers to carefully examine their estimation of the project activities times and the sub-critical path(s) leading to a much improved approach for monitoring and controlling the project.